Accuracy of cervical auscultation in detecting the presence of material in the airway. Issue 6 (16th November 2017) - Nozue, Shinji; Ihara, Yoshiaki; Takahashi, Koji; Harada, Yuka; Takei, Yoshiko; Yuasa, Ken; Yokoyama, Kaoru
Abstract: Several studies have investigated the accuracy of cervical auscultation (CA). However, both the sensitivities and the specificities of CA in detecting dysphagic conditions varied widely among these studies. These wide variations of the accuracy of CA might be caused by differences of the targeted sounds, such as the expiratory sound (ES) and/or swallowing sound (SS). Forty‐six dysphagic patients were served as subjects. Patients who had unoccluded tracheostoma and patients who could not follow the instructions were excluded. During the videofluorographic swallowing study (VFSS), the subjects swallowed 3 ml of yogurt containing barium sulfate. The VFSS images were recorded with acoustic signals including both the swallowing and respiratory sounds detected by our method. Classification of the VFSS images was decided by consensus of the three dentists using a penetration‐aspiration scale (PAS). Recorded VFSS images were classified into the following 2 groups based on PAS: "no or minimum risk group": PAS1–2; and "possible risk group": PAS3–8. As a result of the classification of VFSS findings, 30 samples were evaluated as no or minimum risk group and 16 as possible risk group. Twelve observers including 10 dentists other than 3 dentists who evaluated VFSS images and 2 speech pathologists auditorily diagnosed "negative" and "positive." Sensitivity, specificity, and intra‐rater reliability was calculated for the 3 types of acoustic samples. The sensitivity of the intra‐rater reliability was 60.3% for ES, 76.6% for SS, and 89.9% for ES + SS. The sensitivity of intra‐rater reliability of ES + SS samples was significantly higher than that of ES ( p < .01) and SS ( p < .05). The sensitivity of intra‐rater reliability of SS was significantly higher than that of ES ( p < .01). The specificity of the intra‐rater reliability was 53.7% for ES, 50.3% for SS, and 44.5% for ES + SS. ES + SS might be most useful for detecting the presence of material in the airway.